Thinking with AI (Open Humanities Press, 2025)
This collected volume explores a novel approach to the intersection of artificial intelligence and the humanities, proposing that instead of merely writing about AI, scholars should think with AI. Rather than treating AI as an external subject of study, the essays explore how concepts from artificial intelligence, machine learning, and data science can provide ways to rethink core humanistic questions of meaning, representation, and culture.